Searching the inclusive l gamma E-T + b-quark signature for radiative top quark decay and non-standard-model processes - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We compare the inclusive production of events containing a lepton (á), a photon (γ), significant transverse momentum imbalance (E T), and a jet identified as containing a b-quark, to SM predictions. The search uses data produced in proton-antiproton collisions at s=1.96TeV corresponding to 1.9fb-1 of integrated luminosity taken with the CDF detector. We find 28 áγbET events versus an expectation of 31.0-3.5+4.1 events. If we further require events to contain at least three jets and large total transverse energy, the largest SM source is radiative top-quark pair production, tt̄+γ. In the data we observe 16 tt̄γ candidate events versus an expectation from SM sources of 11.2-2.1+2.3. Assuming the difference between the observed number and the predicted non-top-quark total of 6.8-2.0+2.2 is due to SM top-quark production, we estimate the tt̄γ cross section to be 0.15±0.08pb. © 2009 The American Physical Society.